ANALISIS DETERMINAN NILAI PERUSAHAAN SEKTOR PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Yogaswara (2020)
This research is a quantitative study that aims to determine the effect of profitability, capital structure, liquidity, and corporate value. The study was conducted on property and real estate companies listed on the Indonesia Stock Exchange. The sampling technique uses a purposive sampling method. The selection of samples from 48 property and real estate companies listed on the Indonesia Stock Exchange from 2014 to 2018 produced 32 acceptable companies. The type of data used is secondary data. Data collection techniques for the purposes of this study were carried out with library and documentation techniques. Data analysis was performed using the help of Microsoft Excel 2019 and E-views 10. Panel data regression analysis conducted in this study looked at data types in the form of cross-sections and time series with a significance level of 5%. The test results obtained Profitability stated by Return On Equity (ROE) affects the Firm Value, Capital Structure expressed by Debt to Equity Ratio (DER) influences the Firm Value, and Liquidity stated by Current Ratio (CR) does no effect to Value Company.